Novel affinity pairs "tag-receptor" for the purification of fusion proteins - Pina, Ana Sofia Fidalgo Pombo Mendes (2013)
Fundação para a Ciência e Tecnologia - SFRH/BD/48804/2008 and the project PTDC/BI/65383/2006 assigned to Prof. Cecíla Roque and also to Associate Laboratory REQUIMTE (Pest-C/EQB/LA0006/2011)